Profile of Senior High School Students’ Critical Thinking Skills and The Need of Implementation PBL Model Assisted by Augmented Reality Book - Hanandita Veda Saphira; Binar Kurnia Prahani* (Universitas Syiah Kuala, 2022)
Critical thinking skills of students in Indonesia are still very low, then one way to improve CTS is to collaborate learning with real-world problems that can be found in everyday life with the help of existing technology as a learning tool. The purpose of this research was to find out the profile of students' critical thinking skills and the implementation of problem based learning implementation with assisted augmented reality books in high schools, especially on learning physics with parabolic motion materials. The method research is included in preliminary research with a sample of 190 high school students in Surabaya, East Java. Data collection techniques by sharing critical thinking skills tests, student response surveys and interviews of students and teachers. Then the data is analyzed using qualitative descriptive to represent the results of the reserach. The findings of the study are 1) Students' critical thinking skills are still in the low category. 171 students with low categories, 19 medium categories and none at all high-category students; 2) The lowest indicator of critical thinking skills is interpretation; 3) Teachers still use conventional lecture methods and teaching materials during learning; 4) The implementation of problem-based learning models with integrated AR books is expected to improve students' critical thinking skills on physics materials. It can be concluded that to improve students' critical thinking skills, it is important to innovate learning, especially in physics learning, one of which is the implementation of Problem Based Learning assisted by Augmented Reality books.